Plant responses to heterogeneous environments: scaling from shoot modules and whole-plant functions to ecosystem processes - Mori, Akira; Niinemets, Ülo (Ecological research, 2010)
As environmental conditions strongly uctuate in time and can change in a predetermined manner, for instance during growth and development of surrounding vegetation, acclimation to habitat environmental conditions is the key for survival of plants in changing environments.